Prognostic Factor and Survival Rate Among Breast Cancer Patients’ Post-Surgical Treatment - Raynee Kumilau; Firdaus Hayati; Jerry ES Liew; Siti Zubaidah Sharif; Nik Amin Sahid Nik Lah; Dona Cyreline Chin; Diana Lapai (Gazi Medical Journal)
Objective: The prognosis of breast cancer patients is affected by various types of factors, such as the present stage of illness during the initial diagnosis. The goal of this study is to evaluate the biological factors that can be assessed before breast cancer surgery to predict the outcome of breast cancer surgery for patients who have already undergone the procedure. Methods: STATA was utilised for reviewing and analysing the data obtained from the retrospective review of the breast cancer records, which focused on post-surgical treatment patient outcomes. Patients who underwent breast cancer surgery were analysed using the “Cox proportional hazards regression model” to evaluate the factors that predict survival rates. The data analysis includes 482 of breast cancer patients after surgical procedures. Results: A total of 482 patients with breast cancer had surgical procedures from 2016 to 2019. In terms of survival rate, prognostic factors were associated with a poor prognosis for higher-grade tumours, advanced-stage breast cancers, and invasive lobular carcinoma tumour types. Conclusion: Several clinical and pathological factors influence the overall prognosis and treatment choices. Therefore, it is crucial to adopt the right screening programme to diagnose breast cancer at an early stage. Healthcare practitioners must be aware of various therapeutic methods in the management of cancer to enhance the percentage of survival breast cancer patients